1980
DOI: 10.1002/cne.901920104
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopographic organization in the second somatosensory area of M. fascicularis

Abstract: The second somatosensory area (SII) of awake, untrained cynomolgus monkeys was surveyed with recordings from nearly 1,000 single neurons. A detailed somatotopographic organization could be demonstrated in SII because the majority of these neurons had contralateral, moderate to well-defined receptive fields of < 10 cm2, and because neighboring neurons possessed receptive fields that were only slightly displaced from one another. Different body regions were represented in successive anterior to posterior strips … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
157
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(175 citation statements)
references
References 50 publications
16
157
2
Order By: Relevance
“…Robinson and Burton (1980a) reported that the SII region contains a single cutaneous region flanked by "complex zones" that required active movement to drive the neurons, although these zones are smaller than the anterior and posterior fields reported here. More recently, Burton et al (1995) reported, using tracers injected into areas 3b and 1, that the AP length of the SII region exceeds 7 mm and contains separate anterior and posterior body maps.…”
Section: Are These Separate Areas?contrasting
confidence: 58%
See 3 more Smart Citations
“…Robinson and Burton (1980a) reported that the SII region contains a single cutaneous region flanked by "complex zones" that required active movement to drive the neurons, although these zones are smaller than the anterior and posterior fields reported here. More recently, Burton et al (1995) reported, using tracers injected into areas 3b and 1, that the AP length of the SII region exceeds 7 mm and contains separate anterior and posterior body maps.…”
Section: Are These Separate Areas?contrasting
confidence: 58%
“…Figure 12 shows a map summarizing the SII hand region along with our estimates of the body parts represented in the adjacent cortex. The map is similar in size and location within the UBLS to the map of Robinson and Burton (1980a), whose map consisted of a single cortical area, and to the maps of Burton et al (1995) and Krubitzer et al (1995), whose maps consisted of two separate cortical areas.…”
Section: Are These Separate Areas?mentioning
confidence: 75%
See 2 more Smart Citations
“…The peak activation of the parietal operculum, including S2, was more posteriorly located than in most previously published PET studies of pain in which the stimuli have been induced in the arm (Talbot et al, 1991;Casey et al, 1994Casey et al, , 1996Coghill et al, 1994;Craig et al, 1996;Rainville et al, 1997). In single neuron recordings of S2, it has been shown that the foot area is located more posteriorly than the face area in these structures (Robinson and Burton, 1980b). Andersson and coworkers (Andersson et al, 1997) reported increased activity in anterior parts of S2 when painful stimulation of the hand was compared with painful stimulation of the foot.…”
Section: Discussionmentioning
confidence: 60%